Peran Pendeta dalam Konseling Pranikah untuk Mencegah Terjadinya Perceraian dalam Rumah Tangga - Owen Maickel Mewoh; Alvyn Hendriks (Institut Agama Kristen Negeri Palangka Raya, 2024)
This research explores comprehensively the role of a priest in providing the best pre-marital counseling to prevent divorce in the future for married couples with the research methodology applied is qualitative methods and literature studies as well as exploration of suitability with the perspective of being a priest. Data was obtained through in-depth analysis from various literary sources including texts from various journals and books. The findings from this research unequivocally state that understanding the role of the pastor is very important when providing premarital counseling. The theological implications of these findings provide a deep understanding of the needs and challenges faced by couples who are getting married to carefully follow the premarital counseling provided by a pastor so as to help them in the future when their main household prevents them from falling into divorce.